Red empresarial, estrategia para mejorar la competitividad de las Pymes en chapinero de la ciudad de Bogotá (2019)
This article synthesizes descriptively how, through the creation of business networks, a strategy is generated to improve the competitiveness of small and medium enterprises that are located in the town of Chapinero, in the city of Bogotá far the year 2014.The document presents the dynamics of SME companies in business networks, and in which the two forms of business network formation are established, such as; horizontal and vertical, describing its structure; detailing what are the purposes and objectives of these networks, as well as the processes of conformation.At the same time, it establishes the benefits that these bring to these small and medium-sized companies, the income and participation in them, determining what is the importance of business networks far SMEs. In this sense, it has been possible to relate how horizontal and vertical networks could be formed in the town of Chapinero, taking as a basis the business structure of the productive chains that are related in the present article.